REVIEW AND SYNTHESIS OF VIRTUALIZATION IMPLEMENTATION PRACTICES IN IT PROFESSIONAL TRAINING - Bulhakova, O. F. (Systems and Technologies, 2025)
The digital transformation of contemporary society has fundamentally reshaped the requirements and approaches to education in the field of information technology. This article demonstrates how virtualization technologies transform professional preparation by aligning technical solutions with pedagogically grounded approaches. It examines the capabilities of virtual machines, containerization, software-defined networking (SDN), storage virtualization, and cloud-based remote laboratories for safe and reproducible modeling of instructional environments. The aim is to show how these technologies strengthen hands-on training, optimize costs, expand access, and align learning outcomes with employer expectations. The study presents a review of recent publications and an analysis of typical deployment architectures. It shows that isolation, compatibility, and repeatability enable students to practice complex scenarios safely and accelerate the acquisition of practical skills. At the same time, the study identifies constraints: requirements for network and compute resources, performance overhead in resource-intensive tasks, the need for targeted faculty development, and risks of reduced motivation and interaction in fully online settings. Practical guidelines are proposed, including phased implementation with standardized virtual machine images, development of learner support services, integration of assessment tools, and partnerships with companies for project-based learning. The paper outlines prospects for using artificial intelligence for personalized tutoring, edge computing to reduce latency, extended reality (XR) for intuitive three-dimensional interfaces, and cloud-native and serverless approaches that accelerate scaling and simplify the operation of educational infrastructure. The proposed solutions help reconcile instructional quality, scalability, and cost-effectiveness and increase graduates’ readiness for contemporary professional challenges.